Comparison of pulsed three-dimensional CEST acquisition schemes at 7 tesla: steady state versus pseudosteady state - Khlebnikov, Vitaliy; Geades, Nicolas; Klomp, Dennis W.J.; Hoogduin, Hans; Gowland, Penny A.; Mougin, Olivier (Wiley, 2017)
Purpose: To compare two pulsed, volumetric chemical exchange saturation transfer (CEST) acquisition schemes: steady state (SS) and pseudosteady state (PS) for the same brain coverage, spatial/spectral resolution and scan time. Methods: Both schemes were optimized for maximum sensitivity to amide proton transfer (APT) and nuclear Overhauser enhancement (NOE) effects through Bloch McConnell simulations, and compared in terms of sensitivity to APT and NOE effects, and to transmit field inhomogeneity. Five consented healthy volunteers were scanned on a 7 Tesla Philips MRsystem using the optimized protocols at three nominal B1 amplitudes: 1 mT, 2 mT, and 3 mT. Results: Region of interest based analysis revealed that PS is more sensitive (P < 0.05) to APT and NOE effects compared with SS at low B1 amplitudes (0.7–1.0 mT). Also, both sequences have similar dependence on the transmit field inhomogeneity. For the optimum CEST presaturation parameters (1 mT and 2 mT for APT and NOE, respectively), NOE is less sensitive to the inhomogeneity effects (15% signal to noise ratio [SNR] change for a B1 dropout of 40%) compared with APT (35% SNR change for a B1 dropout of 40%). Conclusion: For the same brain coverage, spatial/spectral resolution and scan time, at low power levels PS is more sensitive to the slow chemical exchange-mediated processes compared with SS.